Modulation of the Hypothalamic-Pituitary-Adrenal Axis by Early Life Stress Exposure - van Bodegom, Miranda; Homberg, Judith R.; Henckens, Marloes J. A. G. (Frontiers in cellular neuroscience, 2017)
Exposure to stress during critical periods in development can have severe long-term consequences, increasing overall risk on psychopathology. One of the key stress response systems mediating these long-term effects of stress is the hypothalamic-pituitary-adrenal (HPA) axis; a cascade of central and peripheral events resulting in the release of corticosteroids from the adrenal glands. Activation of the HPA-axis affects brain functioning to ensure a proper behavioral response to the stressor, but stress-induced (mal)adaptation of the HPA-axis' functional maturation may provide a mechanistic basis for the altered stress susceptibility later in life. Development of the HPA-axis and the brain regions involved in its regulation starts prenatally and continues after birth, and is protected by several mechanisms preventing corticosteroid over-exposure to the maturing brain. Nevertheless, early life stress (ELS) exposure has been reported to have numerous consequences on HPA-axis function in adulthood, affecting both its basal and stress-induced activity. According to the match/mismatch theory, encountering ELS prepares an organism for similar ("matching") adversities during adulthood, while a mismatching environment results in an increased susceptibility to psychopathology, indicating that ELS can exert either beneficial or disadvantageous effects depending on the environmental context. Here, we review studies investigating the mechanistic underpinnings of the ELS-induced alterations in the structural and functional development of the HPA-axis and its key external regulators (amygdala, hippocampus, and prefrontal cortex). The effects of ELS appear highly dependent on the developmental time window affected, the sex of the offspring, and the developmental stage at which effects are assessed. Albeit by distinct mechanisms, ELS induced by prenatal stressors, maternal separation, or the limited nesting model inducing fragmented maternal care, typically results in HPA-axis hyper-reactivity in adulthood, as also found in major depression. This hyper-activity is related to increased corticotrophin-releasing hormone signaling and impaired glucocorticoid receptor-mediated negative feedback. In contrast, initial evidence for HPA-axis hypo-reactivity is observed for early social deprivation, potentially reflecting the abnormal HPA-axis function as observed in post-traumatic stress disorder, and future studies should investigate its neural/neuroendocrine foundation in further detail. Interestingly, experiencing additional (chronic) stress in adulthood seems to normalize these alterations in HPA-axis function, supporting the match/mismatch theory.